-4x+10=0-3x

Simple and best practice solution for -4x+10=0-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x+10=0-3x equation:


-4x+10=0-3x

We simplify the equation to the form, which is simple to understand
-4x+10=0-3x

We move all terms containing x to the left and all other terms to the right.
-4x+3x=0-10

We simplify left and right side of the equation.
-1x=-10

We divide both sides of the equation by -1 to get x.
x=10

See similar equations:

| 8a-3-5a=15 | | 8x^2+5y^2=72 | | m=V/9/2r2 | | -7x-10y=-3 | | 7y-8=12y-8 | | 5v^2-5v/1-v | | -14x-6y=18 | | 6t-3+2t=29 | | -6(x+3)+4x+7=6x+8 | | T=4U/E | | -3-p=5p+21 | | X^2-3ax+2a^2+3a-9=0 | | 5a+b=cfora | | T=AB-2 | | 9x-8+9x=7x+16 | | -x+4x+6=14-2 | | 58a+b=cfora | | 13x-3=5x | | 2b-3+6-8=1-b | | x/(x+1)+x/(x-1)=0 | | 2x/5+3=101/2 | | 4m-y=nform | | 12+4x=8x-8 | | 1/2(8-6h)=5 | | 3x^2-12x+24y-48=0 | | 6-4x=7x-9x+4+2 | | C=15f+8h+5p | | 27x-2+47=180 | | 4z+6z=10 | | 27x-2=47 | | 4(x-3)+2=26 | | 7m+n=2forn |

Equations solver categories